BIMBINGAN PRIBADI-SOSIAL DENGAN MENGGUNAKAN ZOOM MEETING UNTUK MENINGKATKAN KECERDASAN EMOSIONAL SISWA DI SMPN 2 CISARUA - Diesa Mabella Amanda; Wahyu Hidayat; Siti Fatimah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This study aims to improve students' emotional intelligence. The method used by researchers is a qualitative descriptive method. The research was conducted at SMPN 2 Cisarua. Data collection techniques are carried out by observation, interviews and supported by documentation. The guidance counselor and students were observed and interviewed by asking a number of questions which had to be answered supported by documentation for evidence of reporting. The results of this study are: 1) the general profile of students' emotional intelligence 2) the personal-social guidance program using zoom meetings is effective for increasing emotional intelligence. Therefore the results obtained were that the three students at SMPN 2 Cisarua had low emotional intelligence which was categorized as medium.Keywords: personal-social guidance, emotional intelligence, zoom meetings, student